Smart Interactive Arabic Textbook sebagai Respons Kurikulum Merdeka: Analisis Kritis Urgensi Buku Ajar Elektronik Bahasa Arab - Singgar Mantahari Dalimunthe; Sofyan Hadi; Rahmawati Rahmawati; Yasmadi Yasmadi; Hanomi Hanomi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
The implementation of the Merdeka Curriculum requires Arabic teaching materials that are flexible, differentiated, multimodal, and supportive of formative assessment. However, many Arabic classrooms still use printed textbooks or static digital documents, which do not optimally support listening, speaking, independent learning, and rapid feedback. This study aims to analyze the urgency of developing an electronic Arabic textbook based on the Smart Interactive Arabic Textbook model as a response to the demands of the Merdeka Curriculum. This research uses library research with content analysis of Merdeka Curriculum policy documents, Arabic Learning Outcomes, and recent literature on digital Arabic learning, differentiated instruction, multimedia learning, gamification, and digital assessment. The findings show that electronic Arabic textbooks are needed for five main purposes: learning personalization, integration of visual-audiovisual texts, strengthening istima’ and kalam skills, reducing cognitive load, and enabling real-time diagnostic assessment. This article contributes a conceptual model of the Smart Interactive Arabic Textbook as a direction for developing adaptive, interactive, data-informed, and curriculum-aligned Arabic teaching materials.